CLASSICAL LOGICS IN COMPUTER SCIENCE - MIHIȘ, Andreea-Diana; LUPEA, Mihaiela-Ana (2015)
The purpose of this book is to present fundamental concepts and results of classical logics in a formal style and in an explicitly computational way.Applications to automated theorem proving in propositional logic and first-orderlogic are discussed. The studied proof methods are: the resolution method, the semantic tableaux method and the sequent calculus. The paper combines the theoretical presentation of classical logics with numerous examples explained and a rich base of proposed exercises.